Persistent Methicillin-Resistant Staphylococcus aureus Bacteremia: Host, Pathogen, and Treatment - Joshua B. Parsons; Annette C. Westgeest; Brian P. Conlon; Vance G. Fowler (MDPI AG, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a devastating pathogen responsible for a variety of life-threatening infections. A distinctive characteristic of this pathogen is its ability to persist in the bloodstream for several days despite seemingly appropriate antibiotics. Persistent MRSA bacteremia is common and is associated with poor clinical outcomes. The etiology of persistent MRSA bacteremia is a result of the complex interplay between the host, the pathogen, and the antibiotic used to treat the infection. In this review, we explore the factors related to each component of the host-pathogen interaction and discuss the clinical relevance of each element. Next, we discuss the treatment options and diagnostic approaches for the management of persistent MRSA bacteremia.